Knowledge and the Climate Change Issue: An Exploratory Study of Cluster and Extra-Cluster Effects - Galbreath, Jeremy; Charles, David; Klass, Des (Springer Netherlands, 2014)
Climate change, while potentially impacting many industries, appears to have considerable significance to the wine industry. Yet little is known about how firms acquire knowledge and gain an understanding of climate change and its impacts. This study, exploratory in nature and studying firms from the wine-producing region of Tasmania, is one of the first in the management literature to use cluster theory to examine the climate change issue. Firms are predicted to exchange knowledge about climate change more readily with other firms internal to the sub-cluster than with those external to the sub-cluster. The hypothesis does not find support. The study also proposes that the different characteristics of knowledge can either increase or decrease their flows in and around clusters. Specifically, ‘‘public’’ knowledge about climate change is predicted to flow more freely than ‘‘private’’ knowledge about climate change. The hypothesis does not find support. Finally, firms are expected to acquire knowledge about climate change from sources other than cluster-entrenched firms, and in particular peak national industry bodies. The hypothesis finds partial support. A discussion of the findings is presented along with future research directions.